Synthesis, Evaluation of Substituent Effect and Antimicrobial Activities of Substituted (E)-1-(3-bromo-4-morpholinophenyl)-3-phenylprop-2-en-1-one Compounds - Balaji, Selvaraj; Rajarajan, Murugan; Vijayakumar, Renganathan; Manikandan, Venkatesan; Senbagam, Rajamohan; Vanangamudi, Ganesan; Thirunarayanan, Ganesamoorthy (Orbital: The Electronic Journal of Chemistry, 2017)
A series of ten substituted (E)-1-(3-bromo-4-morpholinophenyl)-3-phenylprop-2-en-1-one compounds were synthesized by Crossed-Aldol condensation of 3-bromo-4-marpholino acetophenone with various substituted and unsubstituted benzaldehydes in presence of sodium hydroxide. The entire ten compounds are novel and these have been newly synthesized compounds. The synthesized substituted 3-phenylprop-2-en-1-one were characterized by their physical constants and UV, IR, NMR spectral data. These observed UV absorption maximum (λmax nm) value. The group frequencies of infrared absorption (cm-1) of νCO s-cis and s-trans, deformation modes of νCH out of plane and in-plane, νCH=CH out of plane, ν>C=C<out of plane values, 1H chemical shifts (ppm) vinyl protons, 13C chemical shifts (ppm) carbonyl carbons and vinyl carbons values were correlated with various Hammett substituent constants, and Swain-Lupton parameters using single and multi-regression analyses. From the results of statistical analysis, the effects of substituents on the functional group frequencies were studied. The antimicrobial activities of these synthesized substituted (E)-1-(3-bromo-4-morpholinophenyl)-3-phenylprop-2-en-1-ones have been screened using Kirby-Bauer method. DOI: http://dx.doi.org/10.17807/orbital.v9i1.852